The Role of Islamic Religious Education in Preventing Religious Extremism among Adolescents in Singapore - T. Nathan (https://ejournal.insuriponorogo.ac.id/, 2026)
Religious extremism among adolescents has become an increasing concern in multicultural societies, particularly in countries characterized by religious diversity and rapid digital transformation. In Singapore, where social harmony and interreligious coexistence are strongly emphasized, Islamic Religious Education (IRE) plays an essential role in fostering moderate religious understanding and preventing extremist ideologies among Muslim adolescents. This study aims to examine the role of Islamic Religious Education in preventing religious extremism among adolescents in Singapore by exploring its contributions to moral development, critical religious literacy, social cohesion, and resilience against radical narratives. Employing a qualitative library research approach, this study analyzes academic literature, policy documents, and previous empirical studies concerning religious education, youth radicalization, and Islamic educational practices. The findings indicate that Islamic Religious Education contributes significantly to preventing extremism by promoting balanced religious values, critical thinking, tolerance, and civic responsibility. Furthermore, Singapore’s educational and religious institutions have implemented preventive strategies through contextualized Islamic teachings, interfaith dialogue, and digital literacy initiatives to counter online radicalization. However, challenges related to misinformation, social media influence, and identity crises among adolescents remain important concerns. The study concludes that Islamic Religious Education serves as a critical preventive mechanism against religious extremism when supported by inclusive pedagogy, institutional collaboration, and contextual religious guidance adapted to contemporary adolescent challenges.